Combinations of growth factors for human mesenchymal stem cell proliferation and osteogenic differentiation. Issue 7 (July 2020) - Hefka Blahnova, Veronika; Dankova, Jana; Rampichova, Michala; Filova, Eva
Abstract : Aims: Here we introduce a wide and complex study comparing effects of growth factors used alone and in combinations on human mesenchymal stem cell (hMSC) proliferation and osteogenic differentiation. Certain ways of cell behaviour can be triggered by specific peptides – growth factors, influencing cell fate through surface cellular receptors. Methods: In our study transforming growth factor β (TGF-β), basic fibroblast growth factor (bFGF), hepatocyte growth factor (HGF), insulin-like growth factor 1 (IGF-1), and vascular endothelial growth factor (VEGF) were used in order to induce osteogenesis and proliferation of hMSCs from bone marrow. These cells are naturally able to differentiate into various mesodermal cell lines. Effect of each factor itself is pretty well known. We designed experimental groups where two and more growth factors were combined. We supposed cumulative effect would appear when more growth factors with the same effect were combined. The cellular metabolism was evaluated using MTS assay and double-stranded DNA (dsDNA) amount using PicoGreen assay. Alkaline phosphatase (ALP) activity, as early osteogenesis marker, was observed. Phase contrast microscopy was used for cell morphology evaluation. Results: TGF-β and bFGF were shown to significantly enhance cell proliferation. VEGF and IGF-1 supported ALP activity. Light microscopy showed initial extracellular matrix mineralization after VEGF/IGF-1 supply. Conclusion: A combination of more than two growth factors did not support the cellular metabolism level and ALP activity even though the growth factor itself had a positive effect. This is probably caused by interplay of various messengers shared by more growth factor signalling cascades. Cite this article: Bone Joint Res 2020;9(7):412–420.